2005
DOI: 10.1021/bi048359d
|View full text |Cite
|
Sign up to set email alerts
|

Novel Activity of RGS14 on Goα and Giα Nucleotide Binding and Hydrolysis Distinct from Its RGS Domain and GDI Activity

Abstract: The bifunctional protein RGS14 is both a GTPase activating protein (GAP) for Gialpha and Goalphaand a guanine nucleotide dissociation inhibitor (GDI) for Gialpha. This GDI activity is isolated to a region of the protein distinct from the RGS domain that contains an additional G protein-binding domain (RBD/GL). Here, we report that RGS14 missing its RGS domain (R14-RBD/GL) binds directly to Go and Gi to modulate nucleotide binding and hydrolysis by mechanisms distinct from its defined GDI activity. In brain pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
1
17
1
Order By: Relevance
“…The fact that the BRET signal was never completely abolished in the presence of the RGS14 and G␣ i1 double mutants that ablate G␣ binding to both the GPR and RGS domains (Fig. 2, B and C) is consistent with the existence of a third G protein binding site on RGS14, as has been postulated (51).…”
Section: Discussionsupporting
confidence: 84%
“…The fact that the BRET signal was never completely abolished in the presence of the RGS14 and G␣ i1 double mutants that ablate G␣ binding to both the GPR and RGS domains (Fig. 2, B and C) is consistent with the existence of a third G protein binding site on RGS14, as has been postulated (51).…”
Section: Discussionsupporting
confidence: 84%
“…RGS4-GFP was most abundant in the striatum and amygdala of the subcortex. In situ hybridization using RGS4 riboprobes revealed greater amounts of RGS4 in several regions of the frontal cortex with lower levels in the thalamus and striatum (Erdely et al, 2004;Ha et al, 2013;Heraud-Farlow et al, 2013;Kim et al, 2013;Lener et al, 2013;Li et al, 2013a;Steiner et al, 2014;Stratinaki et al, 2013;Wamsteeker Cusulin et al, 2013).…”
Section: Rgs4mentioning
confidence: 99%
“…Further studies demonstrated that RGS14 interacts with and modulates the GTPSase activity of subunits of heterotrimeric proteins from G i/o families (Cho et al, 2000;Hepler et al, 2005;Traver et al, 2000). Actually, it is well known that RGS14 is implicated in a number of cellular processes, including, lymphocyte functions, centrosome formation and nuclear functions, and stress-induced signaling pathways (Cho and Kehrl, 2007;Cho et al, 2005Cho et al, , 2000Lin et al, 2011;Martin-McCaffrey et al, 2004a;Martin-McCaffrey et al, 2004b;MartinMcCaffrey et al, 2005b;Shu et al, 2007).…”
Section: Rgs14 (A28-rgs14)mentioning
confidence: 99%
“…Mouse RGS14 is a 547 amino acid proteins that has a N-terminal RGS domain, two Ras binding domains, and a GoLoco motif. RGS14 can simultaneously bind GDP-Gα i via it GoLoco motif and act as a GAP for GTP bound Gα i (108,118120). RGS14 can interacts with the monomeric G proteins Rap1, Rap2, and H-Ras (121).…”
Section: G-protein Regulatory Proteinsmentioning
confidence: 99%